PENGARUH PERTUMBUHAN EKONOMI, INVESTASI, PAD TERHADAP KEMISKINAN MELALUI KESEMPATAN KERJA DI PROVINSI JAMBI - Siti Hodijah (Jurnal Ekonomi dan Kebijakan Publik Indonesia, 2017)
The purpose of this research is: (1) to  analyze the influence of economic growth, investment, and the PAD against the province of Jambi employment opportunities; (2) to analyze the influence of economic growth, investment, PAD against poverty through  employment opportunities in the province of Jambi.The result of path analysis for equation of structure I shows that economic growth, investment, and PAD simultaneously have significant effect on job opportunity in Jambi Province during 2001-2015 period. Whileknown that investment has a significant effect on poverty, while economic growth, and PAD has not affect significantly on employment in Jambi Province during the period 2001-2015.From the result of path analysis for equation of structure II, can be conclude that economic growth, investment, PAD, and job opportunity simultaneously have significant influence on poverty in Jambi Province during 2001-2015 period. While PAD partially has a significant effect on poverty in Jambi Province during 2001-2015 period, while the growth of economy, investment, and employment in partial have no significant effect to poverty in Jambi Province.